الآليات القانونية لحماية التوقيع الالكتروني في التشريع الجزائري - شيبه, صوريا (جامعة الوادي.University eloued, 2022)
وفي الأخير نستخلص أن المعاملات الالكترونية عموما والتجارة الالكترونية خصوصا أصبحت جزء من التعاملات اليومية للشخص, مما استوجب توفير الحماية له من أي تزوير أو تحريف ,حيث انتهجت مختلف التشريعات , أنظمة واليات من اجل توفير ذلك, ومنها التشريع الجزائري وذلك من خلال التشفير الالكترونية الذي يعد من الطرق الفعالة المستعملة في حماية البيانات, والذي نص عليه المشرع الجزائري في القانون 04/15 المتعلق بالقواعد العامة للتوقيع والتصديق الالكترونيين. بالإضافة إلى تنظيم مهام جهات التصديق الالكتروني وتحديد التزاماتهم قصد تحقيق الأمان للمتعاملين في المجال الالكتروني, حيث يعد التصديق الالكتروني كضمان لصحة المعلومات والبيانات الموقعة من الشخص ,أي أنها لا يشوبها التزوير ولا التحريف, بالإضافة إلى عمد إنكار الشخص لتوقيعه, أو لأي تصرف آخر صدر منه. Finally, we conclude that electronic transactions in general and electronic commerce in particular have become part of a person's daily dealings, which necessitated the provision of protection against any forgery or distortion. Various legislations have adopted regulations and mechanisms to provide this, including Algerian legislation, through electronic encryption, which is one of the effective methods used to protect data, and which was stipulated by the Algerian legislature in Law 15/04 on general rules for electronic signature and authentication. In addition, the functions of the electronic certification authorities are regulated and their obligations are defined in order to ensure the safety of users in the electronic field. Electronic authentication is considered to be a guarantee of the authenticity of information and data signed by the person, that is, it is free from forgery or distortion, in addition to the person's non-denial of his or her signature or any other behavior.
م.س.ع.أ.22
Keywords: الاليات القانونية – التشريع الجزائري – حماية التوقيع الإلكتروني – المعاملات الإلكترونية; Legal mechanisms - Algerian legislation - protection of electronic signature - electronic transactions.